THE USE OF ENDOSCOPIC LIGATION AND PORTO-SYSTEMIC SHUNTING IN THE TREATMENT STAGE OF CHILDREN WITH PORTAL HYPERTENSION - Voroniak, Dariia; Godik, Oleg (The Ukrainian Scientific Medical Youth Journal, 2021)
The bleeding from esophageal and gastric varices is one of the most dangerous complications in children with prehepatic portal hypertension (PH). The literature sources systematization shows that the question of choosing the variceal bleeding prevention optimal method and timing remains debatable in children. The main purpose of our study was to determine the opti- mal management for the variceal bleeding pre- ventive treatment in children with prehepatic PH. The obtained results indicate that the optimal option of the variceal bleeding prophylactic treatment may be a combination of endoscopic and surgical treatment methods in children with prehepatic PH.